Peran dan Dukungan Keluarga dalam Pencegahan Stunting - Ni'matul Ulya; Putri Andanawarih; Ana Setyowati; Swasti Artanti (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
Stunting is a condition where children under 5 years of age cannot thrive due to chronic malnutrition, especially in the first 100 days of life. This decline has an impact on brain growth and development, thereby increasing the risk of developing chronic diseases in adulthood. Apart from poor nutrition, factors causing stunting are low education or lack of parental knowledge about stunting. One of the causes of a mother's poor or weak womb is that she is not old enough to get pregnant or marries young, which causes several problems during pregnancy which can then give birth to a stunted baby. The aim of this service is to increase parents' knowledge in preventing stunting. The method used in this community service activity is through outreach activities to parents in the Jenggot Village area, Pekalongan City. As a result of this activity, participants' knowledge increased, namely good knowledge by 45.2% compared to 23.8% previously given counseling.